2009
DOI: 10.1111/j.1477-2574.2009.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Bucillamine improves hepatic microcirculation and reduces hepatocellular injury after liver warm ischaemia-reperfusion injury

Abstract: Bucillamine reduces the hepatocellular injury of liver ischaemia reperfusion and improves parenchymal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…We have previously shown that bucillamine has a protective effect against liver IRI, which is related to its maintenance of the liver microcirculation 38 . This study has confirmed our previous findings that bucillamine can reduce warm IRI in the liver, and has studied the possible mechanism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have previously shown that bucillamine has a protective effect against liver IRI, which is related to its maintenance of the liver microcirculation 38 . This study has confirmed our previous findings that bucillamine can reduce warm IRI in the liver, and has studied the possible mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…This also correlates with the decreased histological grading of IRI seen on bucillamine infusion. This co‐related with our earlier observation of increased non‐viable nuclei with propidium iodide on intravital microscopy and its attenuation by bucillamine infusion 38 …”
Section: Discussionsupporting
confidence: 87%
“…During the transplantation, IRI is an unavoidable pathological process in the donor liver and is closely related to the primary non-function of the grafted liver [2]. Existing research [6,11] shows that liver IRI is divided into 2 stages: early injury and late injury, with very complicated mechanisms. Early injury on hepatocytes is directly induced by the cytokines, such as TNF-α, IL-1, and IL-6 released by activated KCs and a large amount of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Effective prevention and treatment for the IRI in the grafted liver can improve the function of the grafted liver and increase the success rate of liver transplantation. Thus, it is currently one of the hot topics in the field of liver surgery [46]. A large number of studies have shown that ischemic preconditioning, which refers to one or more transient IR episodes induced in body tissues or organs that confers a state of endogenous protection of body tissue and cells against subsequent long-term ischemic injuries [7], and drug pretreatment, including more than 8 kinds of drugs [8], can be helpful in the prevention and treatment of the grafted liver IRI [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There is experimental evidence that some pharmacological interventions [46,47] protect against liver IR injury in the animal model. In humans, a systematic review of randomized controlled trials assessing the role of pharmacologic interventions in decreasing IR injury after liver resections showed that some interventions such as methyl prednisolone decrease the enzyme markers of liver parenchymal injury after liver resections but without demonstrating evidence of clinical benefit [13] .…”
Section: Pharmacologic Interventions To Decrease Ir Injurymentioning
confidence: 99%